Genome-wide characterization of cytosine-specific 5-hydroxymethylation in normal breast tissue. Issue 4 (2nd April 2020) - Wilkins, Owen M.; Johnson, Kevin C.; Houseman, E. Andres; King, Jessica E.; Marsit, Carmen J.; Christensen, Brock C.
ABSTRACT: Despite recent evidence that 5-hydroxymethylcytosine (5hmC) possesses roles in gene regulation distinct from 5-methylcytosine (5mC), relatively little is known regarding the functions of 5hmC in mammalian tissues. To address this issue, we utilized an approach combining both paired bisulfite (BS) and oxidative bisulfite (oxBS) DNA treatment, to resolve genome-wide patterns of 5hmC and 5mC in normal breast tissue from disease-free women. Although less abundant than 5mC, 5hmC was differentially distributed, and consistently enriched among breast-specific enhancers and transcriptionally active chromatin. In contrast, regulatory regions associated with transcriptional inactivity, such as heterochromatin and repressed Polycomb regions, were relatively depleted of 5hmC. Gene regions containing abundant 5hmC were significantly associated with lactate oxidation, immune cell function, and prolactin signaling pathways. Furthermore, genes containing abundant 5hmC were enriched among those actively transcribed in normal breast tissue. Finally, in independent data sets, normal breast tissue 5hmC was significantly enriched among CpG loci demonstrated to have altered methylation in pre-invasive breast cancer and invasive breast tumors. Primarily, our findings identify genomic loci containing abundant 5hmC in breast tissues and provide a genome-wide map of nucleotide-level 5hmC in normal breast tissue. Additionally, these data suggest 5hmC may participate in gene regulatory programs that are dysregulated during breast-related carcinogenesis.